TiO2 Electron Transport Layer with p–n Homojunctions for Efficient and Stable Perovskite Solar Cells - Zhao, Wenhao; Guo, Pengfei; Wu, Jiahao; Lin, Deyou; Jia, Ning; Fang, Zhiyu; Liu, Chong; Ye, Qian; Zou, Jijun; Zhou, Yuanyuan; Wang, Hongqiang (Nano-Micro Letters, 2024)
Low-temperature processed electron transport layer (ETL) of TiO2 that is widely used in planar perovskite solar cells (PSCs) has inherent low carrier mobility, resulting in insufficient photogenerated electron transport and thus recombination loss at buried interface. Herein, we demonstrate an effective strategy of laser embedding of p-n homojunctions in the TiO2 ETL to accelerate electron transport in PSCs, through localized build-in electric fields that enables boosted electron mobility by two orders of magnitude. Such embedding is found significantly helpful for not only the enhanced crystallization quality of TiO2 ETL, but the fabrication of perovskite films with larger-grain and the less-trap-states. The embedded p–n homojunction enables also the modulation of interfacial energy level between perovskite layers and ETLs, favoring for the reduced voltage deficit of PSCs. Benefiting from these merits, the formamidinium lead iodide (FAPbI3) PSCs employing such ETLs deliver a champion efficiency of 25.50%, along with much-improved device stability under harsh conditions, i.e., maintain over 95% of their initial efficiency after operation at maximum power point under continuous heat and illumination for 500 h, as well as mixed-cation PSCs with a champion efficiency of 22.02% and over 3000 h of ambient storage under humidity stability of 40%. Present study offers new possibilities of regulating charge transport layers via p-n homojunction embedding for high performance optoelectronics. Highlights: 1 Developing a universal strategy of the p–n homojunction engineering that could significantly boost electron mobility of electron transport layer (ETL) by two orders of magnitude. 2 Proposing a new mechanism based on p–n homojunction to explain inhibited carrier loss at buried interface. 3 Setting a new performance benchmark as high as 25.50% for planar perovskite solar cells employing TiO2 as ETLs.